Influence of food on absorption of erythromycin ethyl succinate. - Thompson, P J (1980)
Erythromycin plasma concentrations were determined in 18 subjects after a single dose (800 mg) of a new formulation of erythromycin ethyl succinate taken immediately before, immediately after, and 1 h after food. Adequate absorption occurred with all treatments, although bioavailability was best when the drug was taken before food. Absorption was delayed by food, with the highest and earliest peak plasma erythromycin levels occurring under fasting conditions.